Changes in shallow-reef community composition along environmental gradients on the East African coast - Porter, Sean N.; Branch, George M.; Sink, Kerry J. (Marine biology, 2017)
Abiotic determinants of community composition on shallow reefs are seldom examined at a scale transcending biogeographic regions, and knowledge for the western Indian Ocean is sparse. To address this deficit, turnover in reef community composition was quantified, using gradient forest analyses, along gradients of nine abiotic variables collected in situ or via remote sensing at 54 sites across and within three bioregions: Tropical Western Indian Ocean (Tropical WIO), Delagoa and Natal, spanning 4800 km of east African coastline (5.2–31.1°S). All oceanographic variables differed significantly among bioregions. At a scale across bioregions, wave height declined northwards, while temperature increased. Values for suspended inorganic sediments, chlorophyll- a concentration [chl- a ], turbidity and nutrients were all lowest in Delagoa, in association with the scarcity of rivers there. The most novel and unexpected finding was that the northwards decline in wave action was more strongly associated with changes in community composition across bioregions than any other variable. Temperature was the second-most important variable at that scale. Within bioregions, temperature and [chl- a ] had strongest relationships with community composition in the Tropical WIO. By contrast, in Delagoa, reef profile, susceptibility to sand inundation and reef heterogeneity were most strongly associated with community composition; and in Natal, depth, turbidity and suspended sediment were foremost. Variables of greatest importance within bioregions distilled to (1) those influencing food/energy supply ([chl- a ], turbidity, depth and suspended sediments), which were of particular importance in the Tropical WIO and Natal bioregions, and (2) those altering sand inundation and small-scale current dynamics of reefs (profile, heterogeneity and depth), which were leading factors in the Delagoa Bioregion.